1996
DOI: 10.1007/s002800050528
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate removal during haemodialysis in a patient with advanced laryngeal carcinoma

Abstract: A 62-year-old patient on long-term haemodialysis who developed an inoperable T2N3Mo squamous-cell carcinoma of the larynx was treated with weekly low-dose methotrexate (MTX) after failing to respond to radiotherapy. The patient was initially given one dose of 10 mg MTX (6 mg/m2) as a 1-h infusion, then he received three further i.v. doses of 20 mg (12 mg/m2). Haemodialysis was performed 15-18 h after each dose and the patient received folinic acid (30 mg i.v.q 6 h) until the MTX concentration was < 0.1 mumol/l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Modern protocols and institution of therapeutic drug monitoring have decreased the likelihood of these events, but in such cases, the management of delayed MTX clearance is of great importance. Previous reports have documented MTX clearance with various levels of success using HD [8,9,10,11], HD with charcoal hemoperfusion [12,13,14], HD with serum exchange [15], HD with plasma perfusion [16], and hemofiltration with plasma perfusion over an anion exchange resin [17]. In our experience, HD was superior to HD with charcoal hemoperfusion [18].…”
Section: Discussionmentioning
confidence: 34%
“…Modern protocols and institution of therapeutic drug monitoring have decreased the likelihood of these events, but in such cases, the management of delayed MTX clearance is of great importance. Previous reports have documented MTX clearance with various levels of success using HD [8,9,10,11], HD with charcoal hemoperfusion [12,13,14], HD with serum exchange [15], HD with plasma perfusion [16], and hemofiltration with plasma perfusion over an anion exchange resin [17]. In our experience, HD was superior to HD with charcoal hemoperfusion [18].…”
Section: Discussionmentioning
confidence: 34%
“…The use of low‐dose methotrexate was studied in hemodialysis patient in two case reports (100,101) . In the first report (101) , methotrexate was administered to a laryngeal carcinoma patient at 6–10 mg/m 2 over a 1‐h infusion weekly. A 4‐h hemodialysis was started 15–18 h after the chemotherapy and repeated 48 h later.…”
Section: Drugs That Need Dose Adjustment In Patients With Renal Dysfumentioning
confidence: 99%
“…The elimination t 1/2 were 22–24 h and 5.5 h with dialysis off and on, respectively. There was no methotrexate‐related toxicity (101) . Another case report also showed that methotrexate at a total dose of 20 mg with leucovorin was safely administered to a patient on regular dialysis (100) .…”
Section: Drugs That Need Dose Adjustment In Patients With Renal Dysfumentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these precautions, the risk of renal impairment after high-dose MTX is still approximately 2% 12. The utility of HD in MTX toxicity has been reported previously, but with variable degrees 3 13. It has been shown that acute intermittent high-flux HD is an effective method of clearing high MTX levels in chronic dialysis patients on high-dose MTX treatment 3.…”
Section: Discussionmentioning
confidence: 95%